PENINGKATAN PEMAHAMAN MASYARAKAT TERHADAP PERLINDUNGAN ANAK DARI TINDAK PIDANA KEKERASAN DI KECAMATAN WOLIO KOTA BAUBAU - MASHENDRA,; WD AL ZARLIANI,; AMRUN KAHAR,; LM KARIM, ,; JAMIL,; , LA ODE DEDI ABDULLAH,; MASDIANA, (KRIDA CENDEKIA, 2022)
Children must be protected, at this time there are many cases of violence against children in which the perpetrators are the closest people either parents, siblings, neighborhoods or schools. Many children who are victims of violence are reluctant to report to parents or obligatory parties because there are feelings of fear and also threats from perpetrators of violence. Children or people around children who know that there has been violence against children do not know how to report to the authorities. In addition, many do not understand the crime of violence against and children because they regard it as a family problem. In this community service program, it provides an understanding of the rules that must be obeyed, and the legal impact on the crime of violence against children, giving them the privilege of being victims of violence against children. The approach to resolving partner issues with programs that have been mutually agreed upon in the service realization period is lecture / counseling accompanied by dialogue, with work procedures to support the methods offered are lectures / counseling and dialogue held in several meetings according to partner needs while still in the term program time. Later in this service program will produce scientific articles in accordance with the plan of activity proposer, while for partners is the increase in knowledge of partners is increasing knowledge about criminal acts of violence against children.